Avaliação da imagem corporal, qualidade de vida, sensibilidade tátil e dor em mulheres com câncer de mama submetidas a intervenção cirúrgica - Bueno, Juliana Nishimura [UNIFESP] (2015)
Make a comparison between the preoperative and the 30th, 60th and 90th day postoperatively the surgical treatment of breast cancer, the image changes body, quality of life, sensitivity and presence and level of women's pain pesquisadas.A body image of the evaluated patients changed after surgery treatment of breast cancer. There was a worsening of the results of postoperative 30, 60 and 90 days before the preoperative evaluation. The quality of life had changes in some aspects assessed by questionnaire EORTC QLQ C30, physical function in postoperative evaluation 60 days significantly improved compared to the preoperative period and the evaluation of the emotional function in the postoperative 30, 60 and 90 days compared the preoperative. The assessment of cognitive function also showed improvement in 30 days after surgery compared to preoperatively. There was a significant deterioration in social function and loss of appetite in the postoperative period of 30 days in relation to pre operative, and also the symptoms of nausea and vomiting and constipation in the postoperative period 90 days. Body image when assessed by questionnaire EORTC QLQ BR23, was significantly worse in the evaluation of postoperative 30 days, as well as breast symptoms in the postoperative 30 and 60 days, and symptoms arm in all evaluated postoperatively. As for the function and satisfaction sexual significant improvement in postoperative 30 days, as well as prospects have improved in all investigated postoperative. The sensitivity and pain was noticeable worsening on all postoperative when compared to the preoperative evaluation.